Valproate-Induced Reproductive Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The relation of antiepileptic therapy to the occurrence of reproductive endocrine disorders in 238 women with epilepsy has been studied at the University Hospital, Oulu, Finland.